2000
DOI: 10.1086/302913
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Search in Canadian Families with Inflammatory Bowel Disease Reveals Two Novel Susceptibility Loci

Abstract: The chronic inflammatory bowel diseases (IBDs)-Crohn disease (CD) and ulcerative colitis (UC)-are idiopathic, inflammatory disorders of the gastrointestinal tract. These conditions have a peak incidence in early adulthood and a combined prevalence of approximately 100-200/100,000. Although the etiology of IBD is multifactorial, a significant genetic contribution to disease susceptibility is implied by epidemiological data revealing a sibling risk of approximately 35-fold for CD and approximately 15-fold for UC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
349
4
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(372 citation statements)
references
References 30 publications
15
349
4
4
Order By: Relevance
“…It is of some interest that this SNP is associated with earlier age of onset, as this variant maps to the IBD5 region, which in an early study was only of genome-wide significance in families with early-onset disease. 35 A more recent genotype-phenotype analysis of this region has not, however, confirmed this association. 47 In the present study, we have demonstrated that the common mutations in the NOD2/CARD15 gene have a low contribution to CD susceptibility in a Scottish population.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…It is of some interest that this SNP is associated with earlier age of onset, as this variant maps to the IBD5 region, which in an early study was only of genome-wide significance in families with early-onset disease. 35 A more recent genotype-phenotype analysis of this region has not, however, confirmed this association. 47 In the present study, we have demonstrated that the common mutations in the NOD2/CARD15 gene have a low contribution to CD susceptibility in a Scottish population.…”
Section: Discussionmentioning
confidence: 94%
“…The Irish CD group comprised 113 patients (77 females and 36 males) with a median age at diagnosis of 27.5 years (IQR [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. This corresponded to 38 patients diagnosed before the age of 40 years (A1) and 21 diagnosed after the age of 40 years (A2).…”
Section: Irish Patient Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…1 UC is a complex polygenic condition, characterized by an inappropriate mucosal immune response within the gut to the commensal bacterial flora, leading to ulceration of the colonic mucosa. 2 Genome-wide screening in UC has demonstrated replicated linkage to several chromosomal regions, including regions on chromosomes 12 3,4 and 19 5,6 termed IBD2 and IBD6, respectively. Within the IBD2 loci lies the lectin-like natural killer (NK) receptor gene NKG2D (KLRK1) located at 12p13.2-p12.3.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is still possible that the RAD50 signal is a result of its LD with other markers within the observed association boundaries. Multiple SNPs in the extended RAD50/IL13 region were previously identified as susceptibility factors for various chronic inflammatory diseases such as Crohn's disease, psoriasis, asthma, and atopic dermatitis (Rioux et al ., 2000; Li et al ., 2008, 2010; Paternoster et al ., 2011). Further studies are therefore needed to identify the functional variant(s) and the underlying molecular mechanisms that predispose(s) to a long and healthy life.…”
mentioning
confidence: 99%